PENGARUH KEPEMIMPINAN DAN STANDAR OPERASIONAL PROSEDUR TERHADAP KINERJA PEGAWAI MELALUI PRODUKTIVITAS KERJA (STUDI PADA PERADILAN AGAMA SE-PROVINSI GORONTALO) - Lukman Alan Tomayahu; Meimoon Ibrahim; Ilyas Lamuda (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study aims to determine the extent of the influence of Leadership and standard operational procedures through work productivity on the Religious Courts of Gorontalo Province. The analytical method used to test the hypotheses of this research utilizes a Structural Equation Model (SEM) approach based on Partial Least Square (PLS) with the assistance of SPSS ver. 26 software for research instrument testing and data analysis requirements, and Smart PLS version 3 for data analysis. The results of this study indicate that (1) Leadership has a positive and significant direct effect on employee performance, (2) standard operational procedures have a positive and significant direct effect on employee performance, (3) work productivity has a positive and significant direct effect on employee performance, (4) Leadership has a positive and significant direct effect on work productivity, (5) standard operational procedures have a positive and significant direct effect on work productivity, (6) Leadership has a positive and significant indirect effect on employee performance through work productivity, and (7) standard operational procedures have a positive and significant indirect effect on employee performance through work productivity.